Regain in body mass after weigh-in is linked to success in real life judo competition - Reale, R.; Cox, G. R.; Slater, G.; Burke, L. M. (International Journal of Sport Nutrition and Exercise Metabolism, 2016)
We examined the relationship between the regain of body mass (BM) after weigh-in and success in real-life judo competition. Eighty-six (36 females, 50 males) senior judoka volunteered for this observational study of an international judo competition. Subjects were weighed at the official weigh-in and one hour before their first competition fight (15-20 hr later). Regain in BM after weigh-in was compared between medal winners and nonmedalists, winners and losers of each fight, males and females and across weight divisions. Heavyweights were excluded from analysis. Prefight BM was greater than BM at official weigh-in for both males and females, with % BM gains of 2.3 ± 2.0 (p = .0001; ES= 1.59; CI95% [1.63, 2.98]) and 3.1 ± 2.2 (p = .0001; ES = 2.03; CI95% [2.30, 3.89]), respectively. No significant differences were found between weight divisions for post weigh-in BM regain. Differences in post weigh-in BM regain were significantly higher in medal winners than nonmedalists for males and females combined (1.4 ± 0.4% BM; p = .0026; ES= 0.69; CI95% [0.05, 2.34]) and for males alone (1.5 ± 0.6% BM; p = .017; ES= 0.74; CI95% [0.02, 2.64]), but not for females (1.2 ± 0.7% BM; p = .096; ES = 0.58; CI95% [-0.02, 2.31]). Differences in BM regain after weigh-in between winners and losers were significant across all fights (0.9 ± 0.3% BM; p = .0021; ES= 0.43; CI95% [0.31, 1.41]) but not for first round fights (0.8 ± 0.5% BM; p = .1386, ES = 0.38; CI95% [-0.26, 1.86]). Winners showed a greater regain in BM post weigh-in than losers. This may reflect the greater magnitude of the BM loss needed to achieve weigh-in targets which also relates to the experience level of successful athletes.